PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT TIRTA INVESTAMA DISTRIBUTION CENTRE KAWASAN - Purnama Sari , Dian (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of Leadership Style, Job Dicipline and Job Motivation on Employees Performance. The population in this study amounted to 295 respondents using the simple random sampling method. The sample obtained was 170 respondents. As independent variable, namely Leadership Style, Job Discipline and Job Motivation, while the dependent variable is Employees Performance. The method of data collection is done by questionnaire. While the data processing and analysis methods used are validity test, reliability test, classic assumption test, and hypothesis test using Statistical Product and Service Solutions (SPSS) software Version 13.0. This research was conducted at Employees of PT Tirta Investama Distribution Center in the Region. The results of the analysis of this study can be seen that the results of t test (partial testing) on ​​the Leadership Style variable have a positive and significant effect on Employees Performance with results (4.842>1.984), Job Discipline no positive effect and no significant effect on Employees Performance with results (1.450 <1.984), and Job Motivation does not have a positive effect and there is no significant effect on EmployeesPerformance with results (0.949 <1.984). The results of the F test (simultaneous testing) can be seen that the variables of Leadership Style, Job Discipline and Job Motivation have a strong and positive effect on Employees Performance with results (11.729> 3.05). The results of the analysis using the coefficient of determination (adjusted R2) is known that 17.5% variable Employees Performance can be explained by variable Leadership Style, Job Discipline and Job Motivation examined in this study and the remaining 82.5% is explained by other factors outside the model.